ANALISA PROSEDUR ADMINISTRASI PENGADAAN BARANG PADA PT HELIX SUKSES MAKMUR TANGERANG - Roy Irawan; Intan Kusuma Dewi; Darma Wijaya; Indra Prana; Shinta Indah Cahyani (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
Procurement of goods carried out using information technology and electronic transactions in accordance with statutory provisions. Procurement of goods electronically and reminded transparency and accountability, increase market access and fair business competition, improve the efficiency of the procurement process, support the monitoring and audit process, the method used in this research is descriptive qualitative, which only describes or describes in general terms about the analysis procurement procedures, this method uses three methods of data collection namely observation, interviews and documentation so as to produce an analysis that procurement of goods carried out by PT Helix Sukses Makmur uses two methods, online and offline and from these two methods known online methods that are often done in procurement goods.